"We Are the Women Our Parents Warned Us Against:" Identity Reconstruction and the Re‐Imagining of Gender After High‐Cost Religious Disaffiliation. Issue 1 (23rd January 2021) - Gull, Bethany
Abstract : This paper examines the identity work of women undergoing high‐cost religious disaffiliation by examining the exit experiences of members of the Church of Jesus Christ of Latter‐day Saint (LDS, Mormon). Previous research into religious change has not fully engaged with the extensive identity work that exiters do as they leave these groups. I propose a stage model of religious exit identity development to expand upon the process of identity transformation during and after high‐cost religious exit. Additionally, I examine how the gender regimes of high‐cost‐religions result in different pathways out and experiences during disaffiliation for women and men. Though constructed to describe high‐cost religious exits, this model may also be helpful in understanding other "high‐cost" exits. A video abstract is available at https://youtu.be/hup3KFXvODs .